An introduction to programming with C++ - Zak, Diane (Cengage Learning, 2016)
Discover the importance of learning C++ with Diane Zak's popular AN INTRODUCTION TO PROGRAMMING WITH C++, 8E. This book's distinctive emphasis clarifies how mastering C++ programming skills will benefit you now and throughout your career. This unique text incorporates a student-focused approach that continually highlights the importance and relevance of the programming concepts you are learning. Memorable new examples portray concepts in action, while abundant new hands-on exercises, including mini-quizzes, Labs, and "Try This" features, guide you in absorbing, practicing, and applying concepts as you progress. Trust AN INTRODUCTION TO PROGRAMMING WITH C++, 8E to keep you enthusiastic about learning as you master the skills of C++.